Cellulose fibers deconstruction by twin-screw extrusion with in situ enzymatic hydrolysis via bioextrusion. (May 2021) - Banvillet, Gabriel; Gatt, Etienne; Belgacem, Naceur; Bras, Julien
Graphical abstract: Highlights: Fibers were efficiently deconstructed by extrusion with in situ enzymatic hydrolysis. Enzymes were recovered by centrifugation and their activity was maintained. CNF were obtained with a continuous process at a constant high solid content. Abstract: The aim of this work was to study the cellulose fibers deconstruction by twin-screw extrusion with in situ enzymatic hydrolysis via bioextrusion, for cellulose nanofibrils (CNF) production. Cellulose pulp was extruded with an optimized screw profile, with or without (reference) the addition of an enzymatic solution. An increase of crystallinity index from 67.0% to 73.7% and decrease of DP from 1003 to 419 were observed with bioextrusion. Direct activity measurements of the enzyme confirmed its activity during the process (sugar content increasing from 0.07 ± 0.004 to 2.38 ± 0.003 mg/mL) and after the process (specific activities around 0.20 CMCU/mL). Enzymes were not deactivated during bioextrusion and could be recycled. CNF properties were higher with bioextrusion compared to reference (respective quality indices of 55.5 ± 2.7 and 39.8 ± 2.8), with a lower energy consumption. This proof of concept could be optimized for the industrial production of highly concentrated CNF.